2007
DOI: 10.1073/pnas.0702602104
|View full text |Cite
|
Sign up to set email alerts
|

Trophic cascade facilitates coral recruitment in a marine reserve

Abstract: Reduced fishing pressure and weak predator-prey interactions within marine reserves can create trophic cascades that increase the number of grazing fishes and reduce the coverage of macroalgae on coral reefs. Here, we show that the impacts of reserves extend beyond trophic cascades and enhance the process of coral recruitment. Increased fish grazing, primarily driven by reduced fishing, was strongly negatively correlated with macroalgal cover and resulted in a 2-fold increase in the density of coral recruits w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
268
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 337 publications
(278 citation statements)
references
References 45 publications
7
268
3
Order By: Relevance
“…Recent analyses suggest that marine protected areas may promote local processes, such as herbivory and coral recruitment (39,40), that limit macroalgal proliferation and promote coral recovery, thereby bolstering coral resilience to large-scale disturbance (7,8,11,41,42). However, because several allelopathic macroalgae (e.g., Dictyota, Chlorodesmis, Galaxaura, Lobophora, Halimeda, Ochtodes) also contain toxins that deter some herbivores (43), developing effective marine reserves may require protecting a diverse herbivore guild that includes species that consume chemically defended macroalgae (18,33,43).…”
Section: Discussionmentioning
confidence: 99%
“…Recent analyses suggest that marine protected areas may promote local processes, such as herbivory and coral recruitment (39,40), that limit macroalgal proliferation and promote coral recovery, thereby bolstering coral resilience to large-scale disturbance (7,8,11,41,42). However, because several allelopathic macroalgae (e.g., Dictyota, Chlorodesmis, Galaxaura, Lobophora, Halimeda, Ochtodes) also contain toxins that deter some herbivores (43), developing effective marine reserves may require protecting a diverse herbivore guild that includes species that consume chemically defended macroalgae (18,33,43).…”
Section: Discussionmentioning
confidence: 99%
“…Such intra-habitat variation may, therefore, have considerable ecological importance. For example, grazing intensity is positively correlated with natural rates of coral recruitment (Mumby et al 2007a), and suggests that intra-habitat variation in grazing may influence the potential recovery rates of corals from disturbance, such as hurricanes. The implication for marine reserve planning is that some areas of Montastraea reef may be much more able to recover from disturbances than others, and could be prioritized within reserve selection algorithms.…”
Section: Mumby 2006mentioning
confidence: 99%
“…Several studies have demonstrated a critical role of herbivores reef fishes in influencing competitive interactions between corals and algae (Mumby et al, 2006(Mumby et al, , 2007Hughes et al, 2007Hughes et al, , 2011, and consequently coral reef resilience (Nyströ m and Folke, 2001;Bellwood et al, 2004). Many of these studies have demonstrated a strong negative relationship between fish grazing intensity (particularly biomass) and algal cover with increasing in coral cover (Arnold, 2010;Smith, 2010;Mumby and Steneek, 2011).…”
Section: Discussionmentioning
confidence: 99%